Epstein-Barr Virus-Positive Natural Killer/T-Cell Lymphoma - Cai, Qingqing; Cai, Jun; Fang, Yu; Young, Ken H. (Frontiers in Oncology, 2019)
Extranodal natural killer/T-cell lymphoma, nasal type (ENKL), is a rare malignancy of Non-Hodgkin lymphoma characterized by an aggressive clinical course and poor prognosis. It shows strong association with Epstein-Barr virus infection and occurs more commonly in Asia and Latin America. Various genetic alterations have been identified in ENKL by gene expression profiling and sequencing techniques. The frequent deletion of chromosome 6q21 was reported to lead to the silence of several tumor suppressor genes. Also, there have been novel genetic mutations that were recently uncovered and were found to frequently activate several oncogenic pathways, including the JAK/STAT, NF-κB and MAPK pathways. Besides, we believe that deregulated single genes and epigenetic dysregulation might be relevant to the mechanism of this disease and thus, may have the potential to shed lights on the development of new therapeutic strategies. The consensus on the standard treatment for ENKL has not yet been currently established. For localized ENKL patients, radiotherapy with concurrent chemotherapy and sequential patterns of chemotherapy and radiotherapy are recommended as first-line therapy. As for advanced or relapsed/refractory ENKL patients, the application of non-anthracycline-containing regimens have significantly improved the clinical outcome, contributing to higher response rate, longer overall survival and progression-free survival. Hematopoietic stem cell transplantation is widely recommended for consolidation after a complete remission or partial remission has been achieved. The anti-programmed death 1 antibody, an immune checkpoint inhibitor, has demonstrated favorable results in treating relapsed or refractory ENKL. Of the current ENKL treatment, researchers are still striving to validate how radiotherapy and chemotherapy should be optimally combined and which of the non-anthracycline-containing regimens is superior. In this review, we summarize the main genetic alterations frequently found in ENKL and their role in providing new insights into the therapeutic targets of this disease, and highlight the recent findings regarding new biologic markers, novel therapeutic strategies applied to this intriguing neoplasm.